Design and Implementation of Prototype Balancing The Car While Drifting - Amirudin Fanani (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2016)
Many cases of car accident in Indonesia, caused by two different factors. The first factor, caused by drivers who can not control his vehicledue to slippery roads, sudden braking, and tire burst. The second factor, caused by vehicles that have not applied technologies complement system in the event of drifting on the sudden braking system. Prototype balance the car while drifting modeling the vehicle system that can reduce the occurence of drifting. Sensor to detect the occurence of drifting is used accelerometer and gyroscope type MPU 6050. Drifting caused by the rear tire slip grooves larger than the front tire. Changes resulting sensor data on sudden changes in motion will be responed by microcontroller arduino leonardo. Selanjutnya, the microcontroller will control the steering and brakes so the car does not happen drifting excessive use PID method to determine the value of the output PWM servo steering and brake servo. Steering and brake components are modeled with a dc standard servo motors. Respon testing the system using PID control takes 1300ms to return to a stable position. Tests using PID control relative oscillation occurs, but takes a bit longer.